Carrot hairy roots (Daucus carota L.) characterisation and optimisation for high β‐carotene extraction - Nga Thi Phuong Mai; Thi Van Anh Le; Bao Chau Nguyen; Nguyen Ha Trang Le; Quang Minh Do (Indonesian Journal of Biotechnology, 2022)
Hairy roots are widely known as a biological system for the production of highly diverse biomolecules. β‐carotene – a precursor for vitamin A – is known to be an anti‐oxidant and anti‐gastric cancer and protection agent against cardiovascular disease, heart disease and stroke. β‐carotene has been chemically synthesised and consumed by humans. However, the chemical process often produces a by‐product that may be harmful to human health. Therefore, this study established a protocol to induce hairy roots (HRs) from a Vietnamese carrot variety and produce natural β‐carotene. The Rhizobium rhizogenes ATCC15834 harbouring Ri plasmid and a Vietnamese carrot variety were used as materials for genetic transformation and HR induction studies. The result showed that approximately 50 HR lines were obtained. Culture medium supplemented with 30 mg/L of sucrose that gave the highest biomass of HR was shown in carrot HR line 30, which had a doubling time of 6.5 days. The highest content of β‐carotene extraction, at 128 mg/100g hairy roots, was achieved with a ratio volume (v/v) of 2‐propanol and plant samples of 20:1, followed by two hours’ incubation with 2‐propanol at 60 °C. Our study reveals a highly efficient protocol for Vietnamese carrot hairy root establishment and multiplication. A very efficient protocol for β‐carotene extraction from the hairy root was established to produce natural β‐carotene that achieves the same β‐carotene quantity as that produced by normal roots. This study provides new insight into the production of high‐content and natural β‐carotene for therapeutic application.